Relation of Workplace Incivility, Prosocial Motivation and Emotional Exhaustion to Thriving of Nurses - Nawaz M; Abid G; Quartey-Papafio TK (Dove Medical Press, 2022)
Muhammad Nawaz,1 Ghulam Abid,2 Tawiah Kwatekwei Quartey-Papafio3 1National College of Business Administration and Economics, Lahore and Institute for Grey Systems and Decision Sciences, GreySys Foundation, Lahore, Pakistan; 2Kinnaird College for Women, Lahore, Pakistan; 3College of Economics and Management, Nanjing University of Aeronautics and Astronautics, Nanjing, People's Republic of ChinaBackground: The study attempt to investigate the impact of individual-level factor (prosocial motivation), negative contextual factor (workplace incivility), and personal resource (emotional exhaustion) on the thriving of nurses.Methods: Primary data from 215 Pakistani nurses were collected and analyzed. Data were analyzed through the Second Synthetic Grey Relational Analysis (SSGRA) and the Regression Analysis.Results: We found that workplace incivility and thriving are negatively associated, whereas prosocial motivation positively influenced thriving. We also found the moderating impact of emotional exhaustion on the associations of workplace incivility-thriving and prosocial motivation-thriving. Both SSGRA and Regression Analysis revealed that the impact of prosocial motivation on thriving is more significant than that of workplace incivility, and moderation can also be found significant.Conclusion: The study suggests that a suitable work environment, appropriate training, and guidance encourage emotional stability and improve prosocial motivation. Similarly, mentoring, socializing, and acknowledging the efforts of nurses' faculty are likely to cope with workplace incivility and promote their thriving.Keywords: workplace incivility, prosocial motivation, emotional exhaustion, thriving, grey relational analysis